Analisis Lingkungan Kerja Pada Dinas Perumahan Rakyat dan Kawasan Permukiman Kabupaten Karawang - Husni Triyandi; Puji Isyanto; Dini Yani (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This study aims to analyze a working environment condition in the Public Housing Office and residential areas. A good work environment will greatly affect the level of employee productivity, this can be seen from the improvement of technology and production methods, production facilities and equipment used, the level of occupational safety and health and the atmosphere of the work environment itself. The method used in doing practical work is the case study method by means of a descriptive analysis approach, namely with a method that searches for collections and processes the necessary data and which is further interpreted and compared with theoretical foundations obtained from several literatures.in addition there is a problem related to the jobdesk given which causes practical work students confusion when carrying out activities.